Emerging PET Radiotracers and Targets for Imaging of Neuroinflammation in Neurodegenerative Diseases: Outlook Beyond TSPO. (8th September 2018) - Narayanaswami, Vidya; Dahl, Kenneth; Bernard-Gauthier, Vadim; Josephson, Lee; Cumming, Paul; Vasdev, Neil
The dynamic and multicellular processes of neuroinflammation are mediated by the nonneuronal cells of the central nervous system, which include astrocytes and the brain's resident macrophages, microglia. Although initiation of an inflammatory response may be beneficial in response to injury of the nervous system, chronic or maladaptive neuroinflammation can have harmful outcomes in many neurological diseases. An acute neuroinflammatory response is protective when activated neuroglia facilitate tissue repair by releasing anti-inflammatory cytokines and neurotrophic factors. On the other hand, chronic neuroglial activation is a major pathological mechanism in neurodegenerative diseases, likely contributing to neuronal dysfunction, injury, and disease progression. Therefore, the development of specific and sensitive probes for positron emission tomography (PET) studies of neuroinflammation is attracting immense scientific and clinical interest. An early phase of this research emphasized PET studies of the prototypical imaging biomarker of glial activation, translocator protein-18 kDa (TSPO), which presents difficulties for quantitation and lacks absolute cellular specificity. Many alternate molecular targets present themselves for PET imaging of neuroinflammation in vivo, including enzymes, intracellular signaling molecules as well as ionotropic, G-protein coupled, and immunoglobulin receptors. We now review the lead structures in radiotracer development for PET studies of neuroinflammation targets for neurodegenerative diseases extending beyond TSPO, including glycogen synthase kinase 3, monoamine oxidase-B, reactive oxygen species, imidazoline-2 binding sites, cyclooxygenase, the phospholipase A2/arachidonic acid pathway, sphingosine-1-phosphate receptor-1, cannabinoid-2 receptor, the chemokine receptor CX3CR1, purinergic receptors: P2X7 and P2Y12, the receptor for advanced glycation end products, Mer tyrosine kinase, and triggering receptor expressed on myeloid cells-1. We provide a brief overview of the cellular expression and function of these targets, noting their selectivity for astrocytes and/or microglia, and highlight the classes of PET radiotracers that have been investigated in early-stage preclinical or clinical research studies of neuroinflammation.